READING LITERACY AND NUMERACY ACHIEVEMENT OF ELEMENTARY SCHOOL STUDENTS: EVIDENCE FROM INDONESIA AND THE INDONESIAN SCHOOL OF SINGAPORE - Fery Muhamad Firdaus; Kurniawati Kurniawati; Octavian Muning Sayekti; Evy Nur Rochmah; Amalia Rizky Ardiansyah (PD PGMI se Indonesia, 2026)
This study aims to compare reading literacy and numeracy achievement of elementary school students in domestic and international educational contexts, specifically between the Indonesian School of Singapore (SIS) and elementary schools in Yogyakarta. A quantitative comparative descriptive design with a cross-sectional survey approach was employed. The sample consisted of approximately 100 fifth-grade students selected through purposive sampling. Data were collected using standardized reading literacy and numeracy tests based on the OECD framework, which had been validated and proven reliable. Data analysis involved descriptive and inferential statistics, including tests of normality, homogeneity, and group differences. The findings reveal that reading literacy achievement remains relatively stable across learning phases but continues to show weaknesses in higher-order thinking skills. In contrast, numeracy exhibits more severe gaps, particularly in reasoning and application skills, with an unexpected regression observed at the upper grade level. These results indicate a substantial literacy–numeracy gap, especially in complex problem-solving abilities. The study highlights the urgent need for early numeracy interventions, a pedagogical shift in mathematics instruction toward conceptual understanding, and systematic integration of higher-order thinking skills in both literacy and numeracy learning to support equitable and sustainable student achievement.